Self-awareness of kindergarten students (Journal of the College of Basic Education, 2022)
The current research aims to identify the self-awareness of kindergarten students, and the significance of the differences in self-awareness of kindergarten students according to the variable of the academic stage. In order to achieve the objectives of the research, the two researchers built a scale of self-awareness and then analyzed the items of the scale logically and statistically to calculate its discriminatory ability and its validity coefficients. For the academic year (2021-2022) the researchers used the descriptive approach randomly. Psychometric properties were extracted from the validity and reliability of the scale and they used appropriate statistical methods to extract them and draw conclusions. Thus, the self-awareness scale consists of (44) items, and the research reached the following results:Kindergarten students are self-aware.There are statistically significant differences in the self-awareness of kindergarten students in the College of Basic Education / Al-Mustansiriya University by academic stage.The first stage students have a higher level of self-awareness than the second, third and fourth stage students